2013
DOI: 10.1097/fjc.0b013e31829013ff
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Nitric Oxide Pathway in the Relaxation Response Induced by E-cinnamaldehyde Oxime in Superior Mesenteric Artery Isolated From Rats

Abstract: For many years, nitric oxide (NO) has been studied as an important mediator in the control of vascular tone. Endothelial deficiencies that diminish NO production can result in the development of several future cardiovascular diseases, such as hypertension and arteriosclerosis. In this context, new drugs with potential ability to donate NO have been studied. In this study, 3 aromatic oximes [benzophenone oxime, 4-Cl-benzophenone oxime, and E-cinnamaldehyde oxime (E-CAOx)] induced vasorelaxation in endothelium-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…These data suggest the involvement of the NO-sGC-cGMP pathway in the relaxant response induced by Oxime S1. In a similar way, Chalupský et al and Veras et al [13,14] demonstrated that the effects of several non-aromatic substituted oximes derivatives involve the NO-sGC-cGMP pathway.…”
Section: Oxime S1 Produces Vasorelaxation Via Activation Of the No-sgmentioning
confidence: 80%
See 3 more Smart Citations
“…These data suggest the involvement of the NO-sGC-cGMP pathway in the relaxant response induced by Oxime S1. In a similar way, Chalupský et al and Veras et al [13,14] demonstrated that the effects of several non-aromatic substituted oximes derivatives involve the NO-sGC-cGMP pathway.…”
Section: Oxime S1 Produces Vasorelaxation Via Activation Of the No-sgmentioning
confidence: 80%
“…It has been reported that non-amino acid compounds sharing the R 2 C=NOH group can produce nitric oxide synthase-independent relaxation in endothelium-denuded aortic rings of rats [10,[14][15][16]. In addition, the mechanisms underlying the effects of exogenous nitrovasodilators are predominantly mediated by cyclic guanosine monophosphate (cGMP), as a result of the activation of soluble guanylyl cyclase [17,18].…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Previous publications reported that aryl oximes could be metabolized by cytochrome P450 and NO synthase to release NO [1, 10, 52]. Because of the biological effects of NO during reperfusion, we studied whether the aryl oxime IQ-1S could act as a NO precursor after an in situ oxidation catalyzed by endogenous enzymes under physiological conditions (liver microsomes with NADPH and O 2 ).…”
Section: Resultsmentioning
confidence: 99%